Optimization of medium composition and study of growth stages of Mycoplasma bovis “Kaluga 2020” isolate - M. Abed Alhussen; A. A. Nesterov; A. V. Sprygin; I. N. Shumilova; M. S. Bryantseva; O. P. Byadovskaya (Ветеринария сегодня)
Mycoplasma bovis is considered one of bovine mycoplasmosis pathogens responsible for respiratory diseases, mastitis, arthritis and keratoconjunctivitis. The paper presents results of the study on optimizing the component composition of the culture medium for Mycoplasma bovis “Kaluga 2020” isolate, as well as the study of this pathogen’s growth stages. The color-changing units assay and the culture method combined with colony-forming unit quantification were used for determination of Mycoplasma activity. It was found that when cultured in an optimized nutrient medium based on modified Hayflick broth, the microorganism enters a logarithmic growth phase after first 24 hours ofgrowth, in 72 hours the Mycoplasma culture enters astability phase, and adecline phase is recorded in 84 hours. The effect of percentage content of glucose, fresh yeast extract and horse serum in the nutrient medium on accumulation of Mycoplasma bovis “Kaluga2020” isolate was evaluated using the one-factor-at-a-time approach. It was found that the greatest effect on Mycoplasma accumulation was exerted by such growth factors as fresh yeast extract and horse serum in the nutrient medium (p < 0.05), while changes in the amount of glucose did not stimulate Mycoplasma bovis growth. Based on results of the conducted studies, the appropriate composition was determined and the optimal content of growth factors in the medium for culturing Mycoplasma bovis “Kaluga 2020” isolate was selected: 12.5%of fresh yeast extract and 25% of horse serum. The use of the optimized nutrient medium based on modified Hayflick broth allowed 5-fold increase in accumulation of Mycoplasma biomass (3.98 × 109CFU/ml)compared to the standard medium (0.79 × 109CFU/ml).